2015
DOI: 10.1097/htr.0000000000000087
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Pragmatic Treatment

Abstract: The results suggest that the CPT program is efficacious in improving communicative-pragmatic abilities in individuals with TBI, and that improvements at this level are still detectable even in chronic patients years after the injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 61 publications
1
29
0
1
Order By: Relevance
“…In line with Gabbatore et al ( 2015 ), we predict a post-training increase of our chronic patients’ communicative performance, as assessed through the equivalent forms of ABaCo (Bosco et al, 2012 ). At the neural level, in line with the previous literature (Yin et al, 2014 ; Lampit et al, 2015 ), we expect that behavioral improvements are accompanied by functional plastic changes in regions involved in the training: explorative imaging analysis should highlight what circuits support such changes.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…In line with Gabbatore et al ( 2015 ), we predict a post-training increase of our chronic patients’ communicative performance, as assessed through the equivalent forms of ABaCo (Bosco et al, 2012 ). At the neural level, in line with the previous literature (Yin et al, 2014 ; Lampit et al, 2015 ), we expect that behavioral improvements are accompanied by functional plastic changes in regions involved in the training: explorative imaging analysis should highlight what circuits support such changes.…”
Section: Introductionsupporting
confidence: 82%
“…Moreover, the protocol works on self-awareness, theory of mind and planning abilities, which are essential aspects of effective communication (Coelho et al, 1995 ; Barkley et al, 2001 ; Champagne-Lavau et al, 2006 ). In our previous work (Gabbatore et al, 2015 ) we demonstrated the efficacy of CPT in the rehabilitation of a group of TBI patients. This result is of great importance because, as TBI patients often show specific pragmatic impairments that undermine the effectiveness and informativeness of communication (e.g., McDonald et al, 2000 ; Bara et al, 2001 ; Carlomagno et al, 2011 ; Coelho et al, 2013 ; Bosco et al, 2015 ), enhancing their communicative-pragmatic abilities can have a major impact on long-term outcome and social reintegration (Togher et al, 2014 ).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Extending treatment to include interventions focusing on the pragmatic skills of individuals with dyslexia should, thus, be of primary interest in order to promote successful access to all levels of education and inclusion across their lifespan. Recently, a number of training programmes to promote pragmatic abilities and figurative language have been developed (Gabbatore et al, 2015;Melogno, Pinto, & Di Filippo, 2017), and we believe that, with proper adjustments, they could be beneficial also for individuals with dyslexia.…”
Section: Figurementioning
confidence: 99%
“…For example they share an impaired ability to go beyond the literal meaning of utterances, and thus to correctly interpret indirect speech acts, metaphors, and irony (see Angeleri et al, 2008 ); moreover, these patients have difficulties in producing requests and exhibit a deficit in integrating information, with low levels of adherence to the context (see Cummings, 2014 ). CPT has already shown to be effective in improving and enhancing communicative-pragmatic abilities in TBI patients ( Gabbatore et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%